2017
DOI: 10.15226/2473-2176/2/2/00118
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid Fever as a Challenge for Developing Countries and Elusive Diagnostic Approaches Available for the Enteric Fever

Abstract: Salmonella typhi is the causal organism for the typhoid fever. Typhoid disease is a problem in those developing countries where lack of sanitation, poor water supplies and exposure to unhygienic and polluted environment is a part of routine life of majority of population. Salmonella typhi expresses various virulence antigens like H-antigens, O-antigens and Vi antigens which plays vital role in the infection and pathogenesis of the bacteria. Salmonella typhi causes fever, nausea, headache, body fatigue and bowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 111 publications
(157 reference statements)
0
12
0
1
Order By: Relevance
“…They are mainly spread in environment from excreta (Delahoy et al, 2018). The genus Salmonella has two distinct species (Salmonella enterica and Salmonella bongori) and includes over 2,500 known serotypes, which are considered potential human pathogens (Bharmoria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly spread in environment from excreta (Delahoy et al, 2018). The genus Salmonella has two distinct species (Salmonella enterica and Salmonella bongori) and includes over 2,500 known serotypes, which are considered potential human pathogens (Bharmoria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In many developing countries, especially in sub-Saharan Africa, the true burden of enteric fever is difficult to estimate due to the limited diagnostic resources and proper surveillance tools result in poor characterization of the burden of enteric fever [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although feces and urine are commonly used samples, it has been reported that S. enterica could be isolated from only about 30% of feces, and less than 1% of urine samples in patients with typhoid fever [ 32 ]. While the culture of duodenal bile samples has shown similar sensitivity as that reported for blood samples, the procedure of sample collection is difficult to tolerate, especially for young children and those with severe disease [ 40 ].…”
Section: Laboratory Diagnostic Approachesmentioning
confidence: 99%